2019
DOI: 10.1021/acs.jpcc.9b01576
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Role of Ru(II) Orbital and Spin Contribution on Photoinduced Ligand Exchange: New Mechanism To Access the Photodynamic Therapy Window

Abstract: A series of 12 Ru­(II) complexes of the type [Ru­(tpy)­(L)­(CH3CN)] n+, 1–12, containing the tridentate tpy ligand (tpy = 2,2′:6′,2″-terpyridine) and various bidentate ancillary ligands, L, were synthesized and evaluated for their ability to photodissociate CH3CN, a model for nitrile-containing drugs. Although the bidentate ligands chosen display a similar degree of steric bulk around the metal center in the ground state, the photosubstitution efficiencies of 1–12 vary by approximately an order of magnitude. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 62 publications
(130 reference statements)
5
34
0
Order By: Relevance
“…In a series of 12 complexes of the type [Ru(tpy)(L)(CH 3 CN)] n+ (tpy ¼ 2,2 0 :6 0 ,2 00terpyridine), where L represents a neutral (n ¼ 2) or an anionic (n ¼ 1) bidentate ligand, the quantum yields for the photosubstitution of the CH 3 CN ligand for a water solvent molecule upon 400 nm irradiation, F 400 , resulted in the unexpected increase of ligand exchange with the increasing electrondonating character of the bidentate ligand, despite the lower 3 MLCT energy across the series. 42 Calculations revealed that as the p-donating ability of the bidentate ligand increased, the relative amount of metal character in the highest occupied molecular orbital (HOMO) decreased. As such, a strong inverse correlation between the % Ru(d) character of the HOMO and the F 400 values was observed.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of 12 complexes of the type [Ru(tpy)(L)(CH 3 CN)] n+ (tpy ¼ 2,2 0 :6 0 ,2 00terpyridine), where L represents a neutral (n ¼ 2) or an anionic (n ¼ 1) bidentate ligand, the quantum yields for the photosubstitution of the CH 3 CN ligand for a water solvent molecule upon 400 nm irradiation, F 400 , resulted in the unexpected increase of ligand exchange with the increasing electrondonating character of the bidentate ligand, despite the lower 3 MLCT energy across the series. 42 Calculations revealed that as the p-donating ability of the bidentate ligand increased, the relative amount of metal character in the highest occupied molecular orbital (HOMO) decreased. As such, a strong inverse correlation between the % Ru(d) character of the HOMO and the F 400 values was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these and related systems have been altered further by introducing a central metal ion into the tetrapyrrolic scaffold to enhance the chemical, photophysical, and biological characteristics of the parent PSs. [29,30] Design of the next generation of PSs has been focused on extending the absorption window to include NIR wavelengths (700-900 nm) [31][32][33][34] and to alter the excited state properties of the molecules to exploit oxygen-independent mechanistic pathways to achieve phototoxic effects in hypoxia. [35][36][37][38][39][40] Ru II polypyridyl complexes are particularly attractive scaffolds for PS design because the photophysics of these complexes is wellestablished [41][42][43][44][45][46][47] and polypyridyl ligand combinations can be chosen to systematically manipulate the excited state dynamics in a rational and consistent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Various Ru II -based NIR scaffolds are known, but their phototoxic effects on cells were not reported. [31][32][33][34]50] Generally, the 1 O 2 quantum yields are low (and PDT effects thus poor) for metal complexes with lowenergy triplet metal-to-ligand charge transfer ( 3 MLCT) excited states due to efficient intersystem crossing (ISC) that competes effectively with 1 O 2 sensitization. [46] To circumvent this issue, we aimed to design Ru II -based NIR complexes with 3 ILCT states that are lower in energy than the 3 MLCT states and much longer lived, due to their organic 3 ππ* character.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations